IMPLEMENTASI VISI DAN MISI SEKOLAH DALAM MEMBENTUK KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA DI SMPIT AR-RISALAH SUKOHARJO - Burhan Haya; Isfihani Isfihani; Iffah Mukhlisah (Jurnal Manajemen Pendidikan, 2026)
This study analyzes the implementation of school vision and mission in shaping the discipline and responsibility character of ninth-grade students at SMPIT Ar-Risalah Sukoharjo in the 2025/2026 academic year. The study employed a descriptive qualitative approach with field research design. Data were collected through non-participant observation, semi-structured interviews, and documentation. The informants consisted of the principal, vice principal for curriculum affairs, Islamic Religious Education teacher, and three ninth-grade students. The data were analyzed through data reduction, data display, and conclusion drawing. Data validity was examined through source triangulation. The findings show that the school vision, “Building a generation with Islamic morals and achievement,” was implemented through character integration in classroom learning, congregational prayer, morning religious routines, class-cleaning duties, flag ceremonies, teacher role modeling, school-rule enforcement, and extracurricular activities. These programs shaped students’ discipline in punctuality, worship, learning, rule compliance, and neatness. Responsibility was developed through learning tasks, class duties, religious roles, flag ceremony assignments, and extracurricular participation. Supporting factors included teacher role modeling, parental support, and an Islamic school environment. Inhibiting factors included peer influence and an external environment that did not fully support character formation.